1937
DOI: 10.1508/cytologia.fujiijubilaei.188
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes and Phylogeny in Some Genera of the Crepidinae

Abstract: To others who have generously sent material of various species, and to the directors of the numerous botanical gardens who have generously sent seeds of many species, we also wish to express our gratitude. We are also much indebted to Mr. Ernest Jund for valuable assistance in growing the cultures and in making the cyto logical preparations, and to the Park Naturalist, Yosemite National Park, and his assistants for their generous cooperation in germinating the seeds of the more difficult species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

1950
1950
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 23 publications
(19 reference statements)
1
38
0
1
Order By: Relevance
“…My own investigations, however, revealed that this achene type (type Ia) is also present in species of the other two main clades. Adylov & Zuckerwanik (1993), reassigned the Central Asian species of Askellia to Youngia, but Askellia differs from Youngia clearly in the chromosome number and in achene morphology: Youngia exhibits compressed and angular ache nes and has a basic chromosome number of x = 8 (Babcock & Jenkins 1937; Y. tenuifolia with x = 5 was transferred to Crepidifolium, see Tzvelev 2008).…”
Section: Tecto Rum)mentioning
confidence: 99%
“…My own investigations, however, revealed that this achene type (type Ia) is also present in species of the other two main clades. Adylov & Zuckerwanik (1993), reassigned the Central Asian species of Askellia to Youngia, but Askellia differs from Youngia clearly in the chromosome number and in achene morphology: Youngia exhibits compressed and angular ache nes and has a basic chromosome number of x = 8 (Babcock & Jenkins 1937; Y. tenuifolia with x = 5 was transferred to Crepidifolium, see Tzvelev 2008).…”
Section: Tecto Rum)mentioning
confidence: 99%
“…Further no systematic and detailed research effort has so far been directed towards the study of chromosome constitution of the two genera Piper and Peperomia with the aid of improved techniques, thus keeping an important lacuna in planning of any significant conclusion of the disputed systematic position of the two genera. In recent years the importance of study of cytology is being more and more appreciated in evolving a natural and phylogenetic system of classification (Babcock et al 1937, Chaudhuri and Sharma 1978, 1979, Sharma 1960, 1967, Sharma and Bal 1956, Sharma and Bhattacharyya 1956.…”
mentioning
confidence: 99%
“…A portion of the hospital space in Manzanar was converted into a workable cytogenetics laboratory where a large volume of material that had primarily been collected elsewhere but grown in Manzanar was examined by Kodani and others (Manzanar Free Press, March 20, 1943). Somatic counts were taken from sections of root tips using the technique developed early for Crepis research (Babcock et al 1937), using vigorously growing seedlings in six-inch pots at Berkeley, while other sections of root tips were taken from cuttings made in the guayule nursery in Manzanar. Meiosis was studied using aceto-carmine smear preparations from plants grown in the fields in Manzanar.…”
Section: é Migré Geneticists In Americamentioning
confidence: 99%